Physical Activity Level Influences MTHFR Gene Methylation Profile in Diabetic Patients - Diniz, Tainá Gomes; Silva, Alexandre Sérgio; dos Santos Nunes, Mayara Karla; Ribeiro, Mateus Duarte; Filho, João Modesto; do Nascimento, Rayner Anderson Ferreira; Gomes, Cecília Neta Alves Pegado; Evangelista, Isabella Wanderley de Queiroga; de Oliveira, Naila Francis Paulo; Persuhn, Darlene Camati (Frontiers in Physiology, 2021)
Introduction: MTHFR methylation status is associated with microvascular complications in diabetes but the factors influencing this profile remain unknow. Objective: To evaluate the influence of physical activity level and nutritional status on the methylation profile of the MTHFR gene in patients with type 2 diabetes mellitus. Methodology: 111 patients, 43 males and 68 women diagnosed with diabetes mellitus (7.0 ± 2.3 years), answered the International Physical Activity Questionnaire (IPAC) and underwent blood collection for biochemical analysis, DNA extraction and MTHFR gene methylation profile determination. Result: The comparison of the methylation pattern showed that the partially methylated profile predominates in the insufficiently active group (85%), which does not occur in the sufficiently active group (54%) (p = 0.012).. No differences were found in the nutritional status comparation. In the logistic regression including overweight, waist circumference, gender, age, time of DM, hypertension, dyslipidemia, smoking, alcoholism, family DM revealed that the association of the level of physical activity with methylation profile proved to be independent of these confounding variables. Considering the partially methylated profile as a result, being physically inactive favors the partially methylated MTHFR pattern in patients with DM. Conclusion: we concluded that insufficient physical activity is associated with partially methylated pattern of MTHFR promoter.